Completeness of the set of sub-σ-algebras - Xikui Wang (International Journal of Mathematics and Mathematical Sciences)
A new metric is introduced on the set of all sub-σ-algebras of a complete probability space from functional analysis point of view. In this note, we will show that the resulting metric space is complete.